PENGEMBANGAN MEDIA DIORAMA SAINS MATERI RANTAI DAN JARING-JARING MAKANAN KELAS V SD - Said, Nurfadillah; Amri Amal; Nasharuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Science education in elementary schools requires a concrete approach to help students understand abstract concepts such as food chains and webs. This study aims to develop a science diorama media based on rice field, sea, and forest ecosystems as an interesting, interactive, and effective learning tool in improving the learning outcomes of fifth grade students. The methodology used is research and development with the ADDIE model (Analyze, Design, Develop, Implement, Evaluate). The media was developed through the stages of needs analysis, visual and instructional design, validation by material and media experts, and limited trials on elementary school students. Data were collected through observation, validation questionnaires, pretests and posttests, and teacher and student responses. The validation results showed that the diorama media was very feasible to use with a feasibility score above 95%. The average student score increased significantly from 52 to 83 after using the media. The results of the N-Gain analysis revealed that most students experienced a high increase in learning outcomes. Teacher and student responses to the media were very positive, stating that the media facilitated understanding of concepts and increased student involvement in learning. This media successfully simplifies the concept of ecology into real visualizations that are easily understood by students of concrete operational age. Science dioramas are proven to be effective as an innovative and contextual science learning solution. This finding has positive implications for improving the quality of learning media in elementary schools and is a reference for the development of similar media on other abstract materials.